The Fungal Pathogen Candida albicans Promotes Bladder Colonization of Group B Streptococcus - Shing, Samuel R.; Ramos, Anissa R.; Patras, Kathryn A.; Riestra, Angelica M.; McCabe, Sinead; Nizet, Victor; Coady, Alison (Frontiers in Cellular and Infection Microbiology, 2020)
Group B Streptococcus (GBS) is a common cause of bacterial urinary tract infections (UTI) in susceptible populations, including pregnant women and the elderly; however, the factors that govern GBS persistence and disease severity in this niche are not fully understood. Here, we report that the presence of the fungus Candida albicans, a common urogenital colonizer, can promote GBS UTI. Co-inoculation of GBS with C. albicans increased bacterial adherence to bladder epithelium and promoted GBS colonization in vivo in a C. albicans adhesin-dependent manner. This study demonstrates that fungal colonization of the urogenital tract may be an important determinant of bacterial pathogenesis during UTI.